Políticas públicas, qualidade de vida e participação democrática: o direito à saúde dos povos indígenas em Roaraima - Anjos, Tereza Cristina Evangelista dos (2008)
This dissertation refers to the state juridical regulation instituted in Brazil with the purpose of protecting, promoting and recovering the indigenous people health through public policies. It intends to analyze if the existing juridical regulation of protection, promotion and recovery of the indigenous health is compatible with the related peculiarities of those people. The recognition of their way of life was constitutionally assured, for the first time in history, through the Brazilian Federal Constitution of 1988 in its article 231. It was verified that the involvement of those people, alone or in a collective way through their communities, as new actors in the social movements, has been generating new and peculiar forms of public policies elaboration. Especially concerning the protection, promotion and recovery of the specific and differentiated health of those people and their communities, the organization of Indigenous Special Sanitary Districts (DSEI’s), which is spaces that materialize and democratize the right to the health of those groups, deserves prominence. At the end of this dissertation, the Eastern Roraima Indigenous Special Sanitary District was analyzed in order to verify it’s potential as instrument of popular participation in the elaboration and in the social control of public policies, taking into account the theoretical model of juridical conception of public policies used in the current dissertation. Key words: Indigenous people, public policies, health, Indigenous Special Sanitary Districts, Brazilian Federal Constitution - 1988